PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA DALAM SISTEM PERADILAN PIDANA DI KOTA JAMBI - Ferdricka Nggeboe (Universitas Batanghari Jambi, 2018)
The marriage bond that is conducted aims to form a happy prosperous household, eternal and lasting under the protection of God Almighty, with the aim, automatically the family should be fostered as well as possible, mutual love and affectionate love between husband and wife and children . Each couple wishes for a harmonious married life, but not forever the condition of the household between husband and wife good and peaceful, because sometimes there are quarrels and bickering, which often leads to the occurrence of violence in the household that eventually happened to a percerarian. The legal policy issued by the Government of the Republic of Indonesia to anticipate violence especially domestic violence is Law Number 23 Year 2004 on the Elimination of Domestic Violence (PKDRT). This law is expected to reveal the various violations in the household and the protection of the rights of victims of violence without exception, therefore the question to be answered in this study is, How to protect the law against women victims of domestic violence in the criminal justice system in the City Jambi. This research uses empirical juridical type, and as its analysis knife the researcher uses legal protection theory, that is preventive law protection and repressive law protection. The emphasis of the analysis on the fact that repressive legal protection in the criminal justice system is reflected from the case reporting process until the case is decided by the judge in court. In addition to a brief overview of the process of domestic violence in the criminal justice system, there are also some judges' decisions on cases with free decisions and verdicts stating that the case was revoked. That the repressive legal protection of victims of domestic violence through the decision of a court of a criminal verdict has shown the comparison of law, although it is still far from the legal certainty.Keywords: Legal Protection Against Women, Domestic Violence Victims, Criminal Justice System